Look at those two!: The precuneus role in unattended third‐person perspective of social interactions. Issue 10 (14th May 2014) - Petrini, Karin; Piwek, Lukasz; Crabbe, Frances; Pollick, Frank E; Garrod, Simon
Abstract Human beings often observe other people's social interactions without being a part of them. Whereas the implications of some brain regions (e.g. amygdala) have been extensively examined, the implication of the precuneus remains yet to be determined. Here we examined the implication of the precuneus in third‐person perspective of social interaction using functional magnetic resonance imaging (fMRI). Participants performed a socially irrelevant task while watching the biological motion of two agents acting in either typical (congruent to social conventions) or atypical (incongruent to social conventions) ways. When compared to typical displays, the atypical displays elicited greater activation in the central and posterior bilateral precuneus, and in frontoparietal and occipital regions. Whereas the right precuneus responded with greater activation also to upside down than upright displays, the left precuneus did not. Correlations and effective connectivity analysis added consistent evidence of an interhemispheric asymmetry between the right and left precuneus. These findings suggest that the precuneus reacts to violations of social expectations, and plays a crucial role in third‐person perspective of others' interaction even when the social context is unattended. Hum Brain Mapp 35:5190–5203, 2014. © 2014 Wiley Periodicals, Inc.